2020
DOI: 10.33774/coe-2020-hvvns
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Political Regimes and Deaths in the Early Stages of the COVID-19 Pandemic

Abstract: This paper provides a quantitative examination of the link between political institutions and deaths during the first 100 days of the COVID-19 pandemic. We demonstrate that countries with more democratic political institutions experienced deaths on a larger per capita scale and sooner than less democratic countries. The result is robust to the inclusion of many relevant controls, a battery of estimation techniques, and to estimation with instruments for the institutional measures that we consider. Additionally… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 0 publications
2
16
1
1
Order By: Relevance
“…For example, the relationship between regime type and COVID-19-related mortality rates is unclear. Some found that authoritarian regimes were more successful in reducing death tolls (Cepaluni et al, 2020;Cheibub et al, 2020). Democracies, to quote one study, "experienced deaths sooner and on a larger scale" (Cepaluni et al, 2020, p. 24), likely because their more delegative nature constrained the capacity to respond rapidly (Malesky and London, 2014).…”
Section: The Role Of Collaborative Governance In Pandemic Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the relationship between regime type and COVID-19-related mortality rates is unclear. Some found that authoritarian regimes were more successful in reducing death tolls (Cepaluni et al, 2020;Cheibub et al, 2020). Democracies, to quote one study, "experienced deaths sooner and on a larger scale" (Cepaluni et al, 2020, p. 24), likely because their more delegative nature constrained the capacity to respond rapidly (Malesky and London, 2014).…”
Section: The Role Of Collaborative Governance In Pandemic Timesmentioning
confidence: 99%
“…Democratic quality also has a variable impact. Some institutions and norms associated with democracy, such as greater transparency or less corruption, have a negative relationship with death reduction (Cepaluni et al, 2020). Other institutions, including rule of law, horizontal accountability, or institutionalised party systems, exhibit no clear relationship (González, 2020).…”
Section: The Role Of Collaborative Governance In Pandemic Timesmentioning
confidence: 99%
“…Evidence suggests that countries with more democratic political institutions experienced more per-capita deaths than less democratic countries do. One explanation is that democratic political institutions generally have a bureaucratic disadvantage in responding quickly to pandemics (Cepaluni et al 2020). In Europe, divergent national responses to COVID-19 reflect different national preferences and political legitimacy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in line with [4], they applied the Corruption Perception Index (CPI) as a proxy for the reliability of reported COVID-19 data. [5] showed that more democratic political institutions experienced deaths on a larger per-capita scale and sooner than did less democratic countries, and based on [6], the population size and government health expenditure are strongly related to COVID-19 cases.…”
Section: Introductionmentioning
confidence: 99%